Qualidade em ambiente de burocracia: o caso da Justiça Federal do Estado do Amazonas - Costa, José Roberto Pimenta Ferreti da (2001)
The necessity to be efficient and effective has long shifted from the private to the public sector. New philosophies have appeared with the aim to supply better performance in both private and public organisms. One of those theories is Quality. It stresses that people who are part of an organisation must realise that they are customers and suppliers within a workflow. The aim of this study was to identify to what extent quality theory can be found in bureaucratic management. The hypothesis was that, despite of the Federal Justice in Amazonas State ─ JF-AM ─ being a bureaucratic organisation, quality parameters are present in the tasks conduction and practice execution. This study was descriptive and explicative. It was a case with bibliographical and field research. As for the means, this research was limited due to both a reduced bibliographical archive pertaining to the comparison between bureaucratic and quality theories, and the uncertainty about the veracity from the questionnaires answers to be answered by members of the sample organisation, the JF-AM. Another limitation factor was the fact that the sample organisation is under the federal judiciary power which excluded views from a State and municipal orbit and from other areas of public power, such as the legislative and the executive. Therefore it seems interesting to gather from this locus another view of quality, mainly as reforms to the judiciary system are in question, which lent a special meaning to this research. The final conclusion was that quality parameters were found in the bureaucratic sample organisation.